Respuesta :
We simply equate the y.
y = x + 9 , y = 2x + 1
Therefore:
y = x + 9 = 2x + 1
x + 9 = 2x + 1.
The answer is the fourth option.
y = x + 9 , y = 2x + 1
Therefore:
y = x + 9 = 2x + 1
x + 9 = 2x + 1.
The answer is the fourth option.
x+9=2x+1
Since both equations give the value of y, therefor y = y. You simply substitute y with its corresponding equation.
y = y
x + 9 = 2x + 1 *we need to find the value of x to get the value of y.
x - 2x = 1 - 9
-x = -8
-1x/-1 = -8/-1
x = 8
Substitute x with its value to get y.
Equation S: y = x + 9 ⇒ y = 8 + 9 ⇒ y = 17
Equation T: y = 2x + 1 ⇒ y = 2(8) + 1 ⇒ y = 16 + 1 ⇒ y = 17
x+9=2x+1
17 = 17
Since both equations give the value of y, therefor y = y. You simply substitute y with its corresponding equation.
y = y
x + 9 = 2x + 1 *we need to find the value of x to get the value of y.
x - 2x = 1 - 9
-x = -8
-1x/-1 = -8/-1
x = 8
Substitute x with its value to get y.
Equation S: y = x + 9 ⇒ y = 8 + 9 ⇒ y = 17
Equation T: y = 2x + 1 ⇒ y = 2(8) + 1 ⇒ y = 16 + 1 ⇒ y = 17
x+9=2x+1
17 = 17